Country Partnership Framework for the Central African Republic for the Period FY21-FY25 - World Bank (World Bank, Washington, DC, 2020)
The Central African Republic (CAR), sparsely populated and landlocked in the heart of the continent, is one of the poorest and most fragile countries in the world despite its wealth in natural resources. The socio-economic and health impacts of the Coronavirus disease (COVID-19) will put additional strain on an already fragile system. CAR is at a critical inflection point, following the signature of an ambitious Peace Accord – with a subsequent sharp decline in violence - and ahead of a double electoral cycle.